2022
DOI: 10.1108/k-09-2021-0818
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of customer knowledge management on the innovative work behavior and product innovation relationship

Abstract: PurposeThe purpose of the present research is to introduce a combined framework that integrates innovative work behavior, product innovation process and customer knowledge management; then, to explore the mediating effect of customer knowledge management in the relationship between innovative work behavior and the product innovation process.Design/methodology/approachThe basis for the present research is a cross-sectional design. Data collection from 154 employees occurred using the following structured questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 168 publications
0
2
0
Order By: Relevance
“…There was a total of twenty-three articles that fulfilled the criteria and were qualified in qualitative synthesis and quality assessment (Youssef & Webster, 2022;Prasetyo, Setyadharma, & Kistanti, 2020a;Silinevica et al, 2016;Prasetyo, 2019;Kazimierska and Grębosz, 2017;Ebarefimia, 2014;Makridis & McGuire, 2023;Manab & Aziz, 2019;Agustia, Haryanto, Permatasari, & Midiantari, 2022;Bansal & Sharma, 2022;Dzikowski, 2022;Prasetyo, Setyadharma, & Kistanti, 2020b;Wang, 2021;Abdulkareem & Naimi, 2022 Durmusoglu, 2007;Hemmert, 2023;Birasnav & Bienstock, 2019;Bratianu, Stănescu, & Mocanu, 2022;Chen, 2022;Sadeghi, Afrazeh, & Mahootchi, 2022;Ferreira, Coelho, & Moutinho, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a total of twenty-three articles that fulfilled the criteria and were qualified in qualitative synthesis and quality assessment (Youssef & Webster, 2022;Prasetyo, Setyadharma, & Kistanti, 2020a;Silinevica et al, 2016;Prasetyo, 2019;Kazimierska and Grębosz, 2017;Ebarefimia, 2014;Makridis & McGuire, 2023;Manab & Aziz, 2019;Agustia, Haryanto, Permatasari, & Midiantari, 2022;Bansal & Sharma, 2022;Dzikowski, 2022;Prasetyo, Setyadharma, & Kistanti, 2020b;Wang, 2021;Abdulkareem & Naimi, 2022 Durmusoglu, 2007;Hemmert, 2023;Birasnav & Bienstock, 2019;Bratianu, Stănescu, & Mocanu, 2022;Chen, 2022;Sadeghi, Afrazeh, & Mahootchi, 2022;Ferreira, Coelho, & Moutinho, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Six articles emphasize the important role of consumer requirements, the creation of a product concept, the creation of a comprehensive design, testing, and commercialization of the product are some of the important stages that make up the new product development process (Youssef & Webster, 2022;Prasetyo et al, 2020a;Prasetyo, 2019;Bansal & Sharma, 2022;Agustia et al, 2022;Bratianu et al, 2022). For competitive companies to survive in the industrial sector and improve the quality of regional economic growth companies' competitiveness, it has to rely heavily on innovation in developing new products to maintain consumers.…”
Section: Resultsmentioning
confidence: 99%
“…There are examples of companies that have planned and approved telework protocols, mostly related to home/family factors and reorganization needs (job restructuring or technological innovation) [66]. Most companies that have previously implemented telework have included this practice in their collective agreements.…”
Section: The Relevance Of the Telework Process In The Current Pandemi...mentioning
confidence: 99%
“…The confirmation of the relationships between the constructs of the theoretical model contributes by showing that Brazilian textile companies apply knowledge management processes to be innovative and implement their products innovation. Knowledge management, supported by determinants such as collaboration in idea exploration, idea advocacy, and encouraging participation in idea implementation, contributes significantly to the product innovation process (Bratianu, C., Stănescu & Mocanu, 2022). In other words, companies seek to update their product portfolios when launching products according to market trends and based on knowledge acquired, stored, and applied.…”
Section: And Conclusionmentioning
confidence: 99%
“…Recently, a study identified that knowledge management, supported by determinants such as collaboration in idea exploration, idea advocacy, and encouraging participation in idea implementation, contributed significantly to the product innovation process (Bratianu, C., Stănescu & Mocanu, 2022). Another study found that product innovation is a strategic driver in bridging the gap between knowledge management and performance for specific companies (Setiyono, Iqbal, Alfisyahr, Pebrianggara, & Shofyan, 2022).…”
Section: Introductionmentioning
confidence: 99%